1989
DOI: 10.1148/radiology.172.3.2772197
|View full text |Cite
|
Sign up to set email alerts
|

Isolated avulsion fracture of the lesser tuberosity of the humerus: report of two cases.

Abstract: Isolated avulsion fractures of the lesser tuberosity of the humerus are exceptionally rare. Two cases are reported here, each involving a 12-year-old boy. The mechanism of injury appears to be a strong external rotatory force applied while the arm is at maximum external rotation and approximately 60 degrees of abduction. In children and adolescents the fracture most likely occurs through the apophyseal plate of the lesser tuberosity (traction epiphysis). In adults, clinical differentiation from the far more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 0 publications
2
39
1
5
Order By: Relevance
“…Most cases that have been previously reported were caused by traction of the subscapularis muscle tendon when abduction and excessive external rotation of the shoulder joint occurred [2][3][4][5]. The fracture in this report was caused by forced extension and internal rotation of the shoulder joint (i.e.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Most cases that have been previously reported were caused by traction of the subscapularis muscle tendon when abduction and excessive external rotation of the shoulder joint occurred [2][3][4][5]. The fracture in this report was caused by forced extension and internal rotation of the shoulder joint (i.e.…”
Section: Discussionmentioning
confidence: 62%
“…Large displaced fractures can easily be seen on plain anteroposterior radiographs, but the axillary view is often necessary to detect smaller fragments with minimal displacement [4,6]. van Laarhoven et al [7] reported that CT image analysis was useful in evaluating the fracture area.…”
Section: Isolated Fracture Of the Lesser Tuberosity Of The Humerusmentioning
confidence: 99%
“…Our patient was unable to describe the exact position and the movement which, at the time of the accident could have caused the injury. The mechanism lesser tuberosity humeral fracture as described in literature appears to be combined, direct trauma to the top of the shoulder resulting in classical greater tuberosity avulsion followed by forced external rotation of the shoulder in a position of abduction [5,6]. In this position, the subscapularis tendon is at maximum voltage.…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the greater tuberosity are accessible by standard diagnostic radiographs shoulder. However, the lesser tuberosity fractures are rarely seen on the radiographs and may go unnoticed by superimposing the detached fragment and humeral epiphysis [6,7]. CT scan helps to confirm the diagnosis and eliminate the possibility of an associated shoulder dislocation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Her right upper limb touched the ground with the shoulder in abduction and external rotation with the elbow and wrist extended, which is the typical mechanism of injury in similar cases [4][5][6] . The patient did not have any history of osteoporosis or other metabolic bone disease and was not on any medication on a regular basis.…”
Section: Case Reportmentioning
confidence: 95%